ANAESTHESTIC MANAGEMENT IN DISASTERS AN ANAESTHETIST’S EXPERIENCE IN “LAMNO” BANDA ACHE, INDONESIA: Anaesthetic Management in Disasters - Janjua, Sarfraz Khan; Ahmed, Shafaq; Tariq, Mohammad; Masroor, Rehan; Kaiyani, Asif Gul; Ishaque, Muhammad (Pakistan Armed Forces Medical Journal, 2006)
Objective: The purpose of this study is to highlight the problems faced by the anaesthesiologist in the field and to mention some of the anaesthetic techniques which have proved useful in such adverse circumstances. Introduction: Responding to the call for help to the victims of Tsunami on December 26 2004, the Pakistan Field hospital (Level II) arrived in Sumatra (Indonesia) and was deployed in a remote island, Lamno, Banda Ache. A total of 11,299 patients were treated including 1164 surgeries, from 12th January 2005 to 26th February 2005. The main problems were non availability of pressurized oxygen source, hostile and adverse circumstances, language barrier and massive number of tsunami victims requiring immediate medical attention. The Boyle’s apparatus could not be used as it requires high pressure gases at 40 to 50 psi. The Oxygen concentrator was the only source of Oxygen. Type of Study: Descriptive Material and Methods: The surgical patients mostly had wounds of extremities which were infected. Majority of the surgical procedures included debridements of the wounds, skin grafting and amputation of the extremities. Most of the surgeries were performed under local and regional anaesthetic techniques. A modified general anaesthetic technique using an oxygen concentrator was devised for those few patients where regional anaesthetics alone were inappropriate. Results: Local anaesthesia was administered to 1055 (90.64%) patients with minor injuries; peripheral regional blocks were administered to 35 (3.0%) patients, spinal anaesthesia to 31 (2.66%) patients and extradural anaesthesia to 17 (1.46%) patients. Eighteen (1.546%) patients were operated under dissociative anaesthesia with Ketamine and 08 (0.687%) patients were administered total intravenous anaesthesia, muscle relaxants, endotracheal intubation, bag valve mask (Ambu’s) ventilation, oxygen supplementation from the oxygen concentrator and local anaesthetic infilteration. The incidence of complications was very low and none of the surgical patients had anaesthesia related morbidity or mortality. Conclusion: Most of the Tsunami affected patients could be managed safely under local anaesthesia, regional blocks or dissociative anaesthesia with Ketamine. The oxygen concentrator proved to be highly useful source of oxygen for a modified general anaesthetic technique without using a proper anaesthesia machine.